The warning (Grand Central Pub, Grand Central Publishing, 2019)
Two roads lead to Mount Hope. None leads out. There's no place to run in a community that's been taken and is being intentionally kept off the grid. A small southern town was evacuated after a freak power-plant accident. As the first anniversary of the mishap approaches, some residents are allowed to return past the national guard roadblocks. Mount Hope natives Maggie and Jordan quickly discover that their hometown is not as it was before. Downed cellular networks fail to resume service. Animals savagely attack humans. And the damaged power plant, where Jordan's father is an engineer, is under military lockdown. As friends and family morph into terrifying strangers, the Maggie and Jordan increasingly turn to each other. Their determination to discover who--or what--has taken control of Mount Hope soon has them in the cross-hairs of a presence more sinister than any they could have imagined.

Gone (Michael Bennett, 6,, 2013)
"A crime lord has declared war on America. Only Detective Michael Bennett knows why. Manuel Perrine doesn't fear anyone or anything. A charismatic and ruthless leader, Perrine slaughters rivals as effortlessly as he wears his trademark white linen suit.Detective Michael Bennett once managed to put Perrine behind bars, the only official in the US ever to accomplish that. But now Perrine is out, and he has sworn to find and kill Bennett and everyone dear to him. Detective Bennett, along with his ten adopted children, their nanny, and his grandfather, are hidden safely on a rural California farm, with guards courtesy of the FBI's witness protection program. Perrine begins to embark on an escalating series of assassinations across the country, killings whose brazenness and audacity bring into question the possibility of safety and law in the US. The FBI has no choice but to ask Detective Bennett to risk it all in Perrine's war on America. With explosive action and fierce villainy that rivals James Bond movies at their best, GONE is the next astounding novel by James Patterson"--

Mistress (Little, Brown and Co, Little, Brown, Hachette Book Group, USA, 2013)
After the beautiful Diana Hotchkiss is found murdered outside her apartment, an obsessive man, Ben, discovers she was leading an illicit double life.

The murder house (Little, Brown and Company, Little, Brown, Findaway World, LLC, 2015)
"Number 7 Ocean Drive is a gorgeous, multimillion-dollar beachfront estate in the Hamptons, where money and privilege know no bounds. But its beautiful gothic exterior hides a horrific past: it was the scene of a series of depraved killings that have never been solved. Neglected, empty, and rumored to be cursed, it's known as the Murder House, and locals keep their distance. Detective Jenna Murphy used to consider herself a local, but she hasn't been back since she was a girl. Trying to escape her troubled past and rehabilitate a career on the rocks, the former New York City cop hardly expects her lush and wealthy surroundings to be a hotbed of grisly depravity. But when a Hollywood power broker and his mistress are found dead in the abandoned Murder House, the gruesome crime scene rivals anything Jenna experienced in Manhattan. And what at first seems like an open and shut case turns out to have as many shocking secrets as the Murder House itself, as Jenna quickly realizes that the mansion's history is much darker than even the town's most salacious gossips could have imagined. As more bodies surface, and the secret that Jenna has tried desperately to escape closes in on her, she must risk her own life to expose the truth--before the Murder House claims another victim"-- Provided by publisher.

Alert (A Michael Bennett novel, 8,, 2015)
"New Yorkers aren't easily intimidated, but someone is doing their best to scare them, badly: why? After two inexplicable high-tech attacks, the city that never sleeps is on edge. Detective Michael Bennett, along with his old pal, the FBI's Emily Parker, have to catch the shadowy criminals who claim responsibility--but they're as good at concealing their identities as they are at wreaking havoc. In the wake of a shocking assassination, Bennett begins to suspect that these mysterious events are just the prelude to the biggest threat of all. Soon he's racing against the clock, and against the most destructive enemy he's faced yet, to save his beloved city--before everyone's worst nightmare becomes a reality" -- Provided by publisher.

Woman of God (Little, Brown and Company, 2016)
"St. Peter's Square, Rome. White smoke signals that a new Pope has been chosen. Is it possible that the new Pope is a woman? The world is watching as historic crowds gather in Rome, waiting for news of a new Pope, one who promises to be unlike any other in the Church's history. Some followers are ecstatic, but the leading candidate has made a legion of powerful enemies. From a difficult childhood with drug addled parents, to a career as a doctor on the front lines in Sudan, to a series of trials that test her faith at every turn, Brigid Fitzgerald's convictions and callings have made her the target of all those who fear that the Church has lost its way dangerous adversaries who abhor challenges to tradition. Locked in a deadly, high-stakes battle with forces determined to undermine everything she believes in, Brigid must convert her enemies to her cause before she loses her faith and her life"--

Texas Ranger (Little Brown & Company, Little, Brown & Company, Hachette Audio, LITTLE, BROWN, 2018)
"Across the ranchlands and cities of his home state, Rory Yates's discipline and law-enforcement skills have carried him far--from local highway patrolman to the honorable rank of Texas Ranger. A tough case in Waco has jeopardized Yates's chances at promotion, and he decides to take time off to recharge with his family in their small-town hometown, Redbud. He arrives and finds a horrifying crime scene--and a scathing accusation: he is named a suspect in the murder of his ex-wife, Anne, a devoted teacher whose only controversial act ever was deciding to end her marriage to a Ranger. In search of the killer, Yates follows the Ranger creed--never to surrender--into the inferno of the most twisted and violent minds he's ever encountered. That code just might bring him out alive." -- back.

The 20th victim (Women's murder club, ,, 2020)
The shooters' aim is as fearsomely precise as their target selection. When Lindsay realizes that the fallen men and women excel in a lucrative, criminal activity, she leads the charge in the manhunt for the killers. As the casualty list expands, fear and fascination with this suspicious shooting gallery galvanizes the country. The victims were no angels, but are the shooters villains . . . or heroes?

The black book (A black book thriller, 2,, 2017)
A devoted Chicago cop from a family of career detectives miraculously survives an attack that kills his partner but that he cannot remember himself, an event that causes him to be charged with double murder and tasked with uncovering what really happened to clear his name.

Run for your life: a novel (Little, Brown and Co, Little, Brown, Hachette Audio, Little, Brown and Company, 2009)
Investigating a series of brutal killings by an assailant who calls himself the Teacher and targets wealthy and arrogant victims, detective Mike Bennett finds himself racing against time to save New York from a deadly plot.

The store (Little, Brown and Company, Little, Brown and Co, 2017)
"Jacob and Megan Brandeis have gotten jobs with the mega-successful, ultra-secretive Store. Seems perfect. Seems safe. But their lives are about to become anything but perfect, anything but safe. Especially since Jacob and Megan have a dark secret of their own. They're writing a book that will expose the Store--a forbidden book, a dangerous book. And if the Store finds out, there's only one thing Jacob, Megan and their kids can do--run for their bloody lives."--Dust jacket.

10th anniversary (The women's murder club, 10,, 2011)
Detective Lindsay Boxer's long awaited wedding celebration becomes a distant memory when she is called to investigate a horrendous crime: a badly injured teenage girl is left for dead, and her newborn baby is nowhere to be found. Lindsay discovers that not only is there no trace of the criminals, but that the victim may be keeping secrets as well. At the same time, Assistant District Attorney Yuki Castellano is prosecuting the biggest case of her life, a woman who has been accused of murdering her husband in front of her two young children. Yuki's career rests on a guilty verdict, so when Lindsay finds evidence that could save the defendant, she is forced to choose. Should she trust her best friend or follow her instinct? Lindsay's every move is watched by her new boss, Lieutenant Jackson Brady, and when the pressure to find the baby begins interfering with her new marriage to Joe, she wonders if she'll ever be able to start a family.

Princess (A private novel, ,, 2018)
When Princess Caroline, third in line to the British throne, hires Jack Morgan to find a close friend before the media finds out, he knows the princess is hiding something.

Second honeymoon (Honeymoon, 2,, 2013)
FBI agent John O'Hara and Special Agent Sarah Brubaker hunt an ingenious pair of serial killers whose victims all seem to be newlyweds.

Cross country: a novel (Alex Cross, Book 14,, 2009)
When the home of Alex Cross's oldest friend, Ellie Cox, is turned into the worst murder scene Alex has ever seen, the destruction leads him to believe that he's chasing a horrible new breed of killer. When the elusive killer's trail turns up in Africa, Alex knows that he must follow. Alone.

Three women disappear (Little, Brown and Company, 2020)
When three female suspects in the murder of an accountant, who was a master manipulator, go missing, Detective Sean Walsh, who has a personal connection to the case, discovers why the women have to stay hidden from both the law and each other.

The 19th Christmas (The Women's Murder Club, 19,, 2019)
Description Not Provided

Alex Cross, run (Alex Cross, 20,, 2013)
Detective Alex Cross arrests renowned plastic surgeon Elijah Creem for sleeping with teenage girls. Now, his life ruined, Creem is out of jail, and he's made sure that no one will recognize him--by giving himself a new face. A young woman is found hanging from a sixth-floor window, and Alex is called to the scene. The victim recently gave birth, but the baby is nowhere to be found. Before Alex can begin searching for the missing newborn and killer, he's called to investigate a second crime. All of Washington, D.C., is in a panic, and when a third body is discovered, rumours of three serial killers send the city into an all-out frenzy. Alex's investigations are going nowhere, and he's too focused on the cases to notice that someone has been watching him--and will stop at nothing until he's dead.

Private Paris (Private, 11,, 2016)
While visiting Private's Paris office, Jack Morgan finds himself in pursuit of a client's granddaughter, who is on the run from a drug dealer and investigating the deaths of several of France's cultural elite.

Count to ten (Private novels, Book 13,, 2017)
Summoned to join a new office in Delhi, former Private India head Santosh Wagh struggles to set aside his personal demons before tackling a case involving murderously corrupt authorities and human remains found at a government site.